(3EOGQI GdYfUQ GdHTQj aj efXeGJ GdCYeGd GdMOjKIs - (3RGgO eMeO(B, (3OjQjs; (3SYGOI QGZH GdcShGfj(B, s ((3YeGf(B:s (3OGQ cfhR GdeYQaI(B,s, 2008)
(3GdJWhQ GdJGQjNj dGOGQI GdGaQGO GdMOjKI , GdYdGbGJ GdGfSGfjI h GOGQI GdGaQGO , GdOGaYjI h GdMGLGJ GdGfSGfjI , GdGfeGW GdbjGOjI h GdeGN GdJfXjej , JMdjd h JhUja GdhXGFa , Jbjje GdGOGA , GdJOQjH , JQbjI GdGaQGO aj GdefXeGJ , GdYdGbGJ GdYeGdjI , GdYedjI GdGOGQjI aj eLGd GdGaQGO (B.s
(3eQGLY U(B.320s
Keywords: (3EOGQI GdCaQGOs; (3GdYdGbGJ GdYGeIs; (3GdefXeGJs; (3GdehGQO GdHTQjIs